The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/bmt.2015.320
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of fatigue in patients with moderate to severe chronic GvHD

Abstract: Although fatigue is common after allogeneic hematopoietic cell transplantation, little is known about fatigue in patients with chronic GvHD (cGvHD). The aim of this study was to explore factors associated with fatigue in cGvHD. Data were drawn from a sequentially recruited, cross-sectional study of adults with moderate or severe cGvHD (n = 263). Respondents were classified as fatigued or not fatigued based on their response to a single item regarding loss of energy from the Lee cGvHD Symptom Scale. In univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…This implies that prior research has focused on patients within the first 100 days after transplant in which fatigue is highly prevalent and can occur in up to 90% of the patients [5]. Yet, studies in HSCT have shown that fatigue may persist for long after day 100 [6][7][8] and therefore studies are needed to evaluate complementary therapies not only during the initial 100 days after transplant, but also during the extended survivorship period. In summary, none of the studies provided definitive evidence of the benefit for any of the therapies discussed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This implies that prior research has focused on patients within the first 100 days after transplant in which fatigue is highly prevalent and can occur in up to 90% of the patients [5]. Yet, studies in HSCT have shown that fatigue may persist for long after day 100 [6][7][8] and therefore studies are needed to evaluate complementary therapies not only during the initial 100 days after transplant, but also during the extended survivorship period. In summary, none of the studies provided definitive evidence of the benefit for any of the therapies discussed.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that evaluated fatigue in 76 adult allogeneic HSCT recipients, 68% reported fatigue on the day of transplant, 90% at day 30, and 81% at day 100 posttransplant [5]. Despite that fatigue tends to improve after day 100, studies in HSCT survivors have shown that some level of fatigue may persist for years after the initial 100 days [6][7][8]. In a study that evaluated the quality of life in 406 adult HSCT survivors, investigators found that 56% of the patients continued to suffer from fatigue for 1-3 years after transplant [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cure or control of the underlying primary disease and effective management of transplant-related late complications, may not be accompanied by a full recovery of health status. Late complications including symptom burden (pain, fatigue, insomnia) and chronic graft-versus-host-disease (cGVHD) associated functional impairments are a major contributor to impairments in quality of life among HCT survivors [2][3][4][5]. Given these difficulties, patients may find it challenging to engage in or resume valued activities and daily roles that support higher levels of social well-being including sustaining intimate relationships and participating in activities with friends or family [6].…”
Section: Introductionmentioning
confidence: 99%